Hybrid Learning Spaces and Social Interaction: Reimagining Collaborative Education after the Pandemic - Farikhul Farikhul; Zeynaddin Musennif Shabanov (Global Education : International Journal of Educational Sciences and Languages, 2025)
This study compares hybrid and traditional face-to-face learning environments to assess their impact on student collaboration, engagement, and social interaction. Hybrid learning models combine in-person and online instruction, providing flexibility but also introducing challenges in maintaining meaningful student interactions, particularly for remote learners. The primary objective of this research is to evaluate the effectiveness of hybrid classrooms in fostering social engagement, collaboration, and peer relationships compared to traditional classrooms. A comparative design was employed, with data collected through interviews, observations, and surveys to measure student engagement, satisfaction, and collaboration. The findings indicate that while hybrid learning offers flexibility, it often leads to reduced social presence and collaboration quality, especially for remote students. Traditional classrooms, on the other hand, foster stronger peer relationships and dynamic in-person collaboration. The study suggests that hybrid learning spaces can be improved by integrating advanced communication tools and designing activities that encourage interaction between remote and in-person students. The research emphasizes the importance of creating balanced learning environments that promote both flexibility and social engagement. Future research is recommended to explore the long-term effects of hybrid learning on student collaboration and engagement and to identify strategies to enhance the effectiveness of hybrid models.